2004
DOI: 10.1109/tmag.2004.830220
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Mark Size Dependence on Field Emission Voltage in Heat-Assisted Magnetic Probe Recording on CoNi/Pt Multilayers

Abstract: A method of heat-assisted magnetic recording (HAMR) potentially suitable for probe-based storage systems is characterized. In this work, field emission current from a scanning tunneling microscope (STM) tip is used as the heating source. Pulse voltages of 2-7 V with a duration of 500 ns were applied to a CoNi/Pt multilayered film. Different types of Ir/Pt and W STM tips were used in the experiment. The results show that thermally recorded magnetic marks are formed with a nearly uniform mark size of 170 nm when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…The mark size is determined as the full-width half-maximum (FWHM) of the MFM signal. Similar to our previous work [7,8], the written marks are magnetic in nature and the writing is reversible. Fig.…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…The mark size is determined as the full-width half-maximum (FWHM) of the MFM signal. Similar to our previous work [7,8], the written marks are magnetic in nature and the writing is reversible. Fig.…”
Section: Methodssupporting
confidence: 67%
“…Nakamura et al [6] demonstrated this writing method with an STM several years ago, and saw a mark size that increased with increasing tip voltage. We have also demonstrated the process previously [7,8], but saw very little dependence of mark size on tip voltage above a certain writing threshold. In this work, we complete the model of heat transfer in a multilayered film structure based on the classical Fourier's equation [9] that quantitatively explains the effect of different substrates in mark size, and mark size dependence on pulse voltage.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…This has the possibility of very high spatial resolution as scanning tunneling microscopy (STM), which shows atomic resolution in surface observation [6][7][8]. Some previous work has been done on the demonstration of the STM-based HAMR process on a perpendicular medium [9][10][11][12], but the theoretical model of the write current has not been published yet. In this work, I demonstrated the recording process using different STM tips and completed the model of the writing current based on the Fowler-Nordheim theory [13].…”
Section: Introductionmentioning
confidence: 99%